2012
DOI: 10.1123/jpah.9.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physical Activity at Two Time Points During Pregnancy

Abstract: Background Correlates of prenatal physical activity can inform interventions, but are not well-understood. Methods Participants in the Pregnancy, Infection, and Nutrition 3 Study were recruited before 20 weeks gestation. Women self-reported frequency, duration, and mode of moderate and vigorous physical activities. We used logistic regression to identify correlates of any physical activity (≥10 minutes/week of any mode), any recreational activity (≥10 minutes/week), and high volume recreational activity (eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
4
11
0
Order By: Relevance
“…6,20,27 In contrast, studies of primarily non-Hispanic white women found parity to be positively associated with becoming insufficiently active during pregnancy; 11,15,19,28,29 however, these studies assessed only sports/exercise. Household/caregiving activities make up the majority of total pregnancy activity among Hispanics.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…6,20,27 In contrast, studies of primarily non-Hispanic white women found parity to be positively associated with becoming insufficiently active during pregnancy; 11,15,19,28,29 however, these studies assessed only sports/exercise. Household/caregiving activities make up the majority of total pregnancy activity among Hispanics.…”
Section: Resultsmentioning
confidence: 94%
“…10 The majority of prior studies that examined pregnancy physical activity were conducted in predominantly non-Hispanic populations and were often limited by assessment tools not validated in pregnant women or focused exclusively on sports/exercise. 7,1120 …”
Section: Introductionmentioning
confidence: 99%
“…In general, study findings suggest that there are positive beliefs that prenatal PA contributes to overall well-being (Doran & O’Brien, 2007), stress relief (Duncombe, Wertheim, Skouteris, Paxton, & Kelly, 2007; Rich, Currie, & McMahon, 2004), easier labor/delivery (Rutkowska & Lepecka-Klusek, 2002), reduced depressive/anxiety symptoms (Leiferman, Swibas, Koiness, Marshall, & Dunn, 2011), enjoyment of PA (Jukic et al, in press), and after the baby is born, an enhanced maternal-infant relationship (Rich et al, 2004). Sociodemographic factors known to influence PA beliefs and behaviors include education and income (Evenson et al, 2004; Grace et al, 2006; Ning et al, 2003), age (PA frequency/duration declines with advancing maternal and gestational age; Haakstad, Voldner, Henriksen, & Bo, 2009), and parity (first-time mothers more likely to engage in PA than multiparous mothers; Cramp & Bray, 2009; Grace, Williams, Stewart, & Franche, 2006; Ning et al, 2003).…”
Section: Empirical Evidence: Determinants Of Prenatal Physical Activitymentioning
confidence: 99%
“…Despite the benefits of PA and recommendations that women continue to be active during pregnancy, many women reduce their activity levels during pregnancy and most are not sufficiently active . For example, a study in the USA found that less than 20% of pregnant women were meeting the recommended levels of PA . Pregnancy represents an opportunity to promote PA, as women receive close medical attention and are often highly motivated to improve their health to benefit their children …”
Section: Introductionmentioning
confidence: 99%